Innovative Thinking Approach in Designing Teaching Materials for Ilm Badi Course: A Comprehensive Framework for Enhancing Students' Writing Skills - Muhammad Dalle; Muhammad Jundi; M. Abdul Hamid; Umi Machmudah (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
Students face several challenges in learning Ilm Badi, including difficulty understanding learning objectives, a lack of comprehension regarding the classification in Ilm Badi materials, insufficient visual stimuli in teaching materials, and challenges in generating new sentences. These issues indicate a mismatch between theoretical understanding and practical language skills. Therefore, this study aims to design teaching materials for Ilm Badi with an innovative thinking approach to stimulate students' writing creativity. The research method employed is Research and Development (R&D), integrating the instructional material design procedure by Sa'ud with the ADDIE model. Data were collected through interviews, observations, and questionnaires. The results indicate that the innovative thinking approach is relevant in strengthening creative thinking processes in general and supports the teaching of Ilm Badi with a more progressive and contextual approach. The teaching materials produced through detailed design stages involve composing content in Arabic and Indonesian, utilizing additional visualizations, and designing exercises to encourage students' innovative thinking abilities. The teaching materials design process includes collaboration with relevant experts. It undergoes expert assessments, resulting in teaching materials that meet standards for use in Ilm Badi learning, emphasizing innovative thinking. Further studies are necessary to test the designed teaching materials' effectiveness empirically.